Pedagogies of Meaning in the Health Sciences: Capturing and Promoting a Movement - Walker, Maria Rosa (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
The pedagogy of meaning is a pedagogical approach that intends to facilitate not only the technical training of students but also their human development. However, we can miss some aspects of education, such as subjetivity and meaning, for example. The student´s tutor is somebody who can “capture the internal movement” of the student, and facilitate his/her development. On the other hand, a subtle movement toward the acquisition of virtues can be much more relevant. In this paper we describe the pedagogical principles and practices that can help us for the search of meaning, conflating the principles and perspectives of andragogy and humanities. The authors cited (Torralba, Jane Vella, and Alfonso López Quintás) give us some clues that can help us to go farther than just technological learning, namely, the consideration of generative themes of students, the perception process in learning, and the integration of tradition treasures and cultural context.